Fusarium graminearum and deoxynivalenol contamination in the durum wheat area of Argentina - Lori, Gladys Albina (2003)
Fusarium graminearum head blight of wheat is a destructive disease of the world's wheat-growing areas. This work was performed to analyze the distribution and contamination of deoxynivalenol (DON) and its relationship with F. graminearum kernel invasion in Argentina durum wheat area during two consecutive harvests. A total of 147 samples (cultivars and lines) of durum wheat from 5 locations of the major cropping area (Southern Buenos Aires Province) were analyzed. Percentage of F. graminearum kernel infection was evaluated following the blotter test (ISTA method) and fusarotoxins were analyzed by thin layer chromatography. None of the varieties and lines were free of F. graminearum infection. In the first harvest fungal invasion was very low. From 40 samples, 55% showed DON contamination but only 4 samples (10%) were higher than 2 ppm. In the second harvest, a crop year conducive to scab development, the highest level of F. graminearum kernel invasion observed was 42% on a sample from the humid area (eastern Buenos Aires Province) DON was detected in 47 (78.2%) of 60 samples analyzed and 19 (31.6%) showed levels of DON higher than those established in the guidelines in Canada and USA for food and feedstuff. In both years all locations situated in the humid area showed levels ranging from 0 to < 8 ppm. Within the durum wheat area differences among locations were found. This analysis indicates the need for more information on the problem and distribution of Fusarium mycotoxins in durum wheat grown in Argentina.